Revisiting the Stimulus, Organism, Response Model in AI-Driven Tourism: A Multi-Path Analysis of Personalization, Perception, and Privacy - Arnas Hasanuddin; Achmad Ansari Hasanuddin; Askari Hasanuddin; Sitti Mujahida Baharuddin (STI Policy and Management Journal, 2025)
This study revisits the Stimulus, Organism, Response (S-O-R) model to examine the psychological mechanisms underlying tourists’ responses to AI-based personalization on digital tourism platforms. Drawing on a sample of 360 Indonesian respondents collected via online survey, the research investigates how AI-driven personalization influences three organismic states perceived value, trust, and privacy concern and how these states affect tourists’ behavioral intentions. Using partial least squares structural equation modeling (PLS-SEM), the results reveal that personalization significantly enhances perceived value and trust, while also reducing privacy concern. Each of these organismic responses, in turn, significantly shapes behavioral intention, confirming the relevance of the extended S-O-R framework in the AI tourism context. Theoretically, the study contributes to tourism literature by integrating both positive and negative psychological reactions into a unified explanatory model, highlighting personalization’s dual role as both functional and ethical stimulus. Practically, the findings offer insights for tourism platforms to design AI services that are not only adaptive and efficient but also transparent and trust-enhancing. Limitations include the study’s cross-sectional design and geographic concentration, pointing to future research directions involving longitudinal analysis, cross-cultural comparisons, and exploration of moderating variables such as digital literacy and cultural norms.